Pengaruh Berbagai Perlakuan Fisik Terhadap Molekul dan Aktivitas Protein Antibakteri dalam Cairan Selom Cacing Tanah Perionyx Excavatus - Yumaihana Yumaihana; zeily nurachman (Universitas Andalas, 2007)
Earthworms are invertebrate with the unique immune system, since they are able to hold out bacterium pathogen in growing medium. Their immune system consists of a lot of reactions including: fagocytosis, encapsulation, agglutination, opsonisation and lysis for foreign component attacked. There are some small molecules and extra cellular proteins dilute in coelomic earthworm that play at important role in immune system and antibacterial agent. The present experiment was done to study the effect of several different treatments (feeding, living, medium, electricity stimulation) on the molecules resistance and activity of anti bacterial protein in coelomic of earthworms. Coelomic dilution was extracted by using electricity stimulation at 6 volt, and the activity of anti bacterial protein was measured by spectrophotometer, and agar diffusion. Protein extra cellular molecular size in coelomic dilution was observed by Sodium Duodecil Sulphate (SDS) electrophoresis. Results showed that the activity of anti bacterial protein in coelomic dilution, and molecule with 29 kDa size were deleted by tretments. Extraction of coelomic dilution which contained of activity of anti bacterial protein could be done in feces from cow which was never stimulated before.